Nghị quyết Miễn nhiệm chức vụ Chủ nhiệm một số Ủy ban của Quốc hội khóa XIV (Nghị quyết số: 146/2021/QH14) - Quốc hội (2021)
Toàn văn Nghị quyết Miễn nhiệm chức vụ Chủ nhiệm một số Ủy ban của Quốc hội khóa XIV (Nghị quyết số: 146/2021/QH14)